2013
DOI: 10.1002/mop.27662
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the quality factor of the optical half‐wavelength resonator

Abstract: An electrodynamic analysis of an optical resonator comprising a half‐wavelength dielectric layer that is covered from both sides by quarter‐wavelength layers with higher and lower refractive indices (RIs) is carried out.For such a resonator, the dependences of the external quality factor on number and RIs of the layers are obtained first. That allows one to determine minimum number of the layers in the structure to achieve the required quality factor at practically any contrast of the RIs. The results of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It is clear that the roots, ω n , of the equation 1/Annormale(ω)=0 for each multipole excitation of the nanoparticle are the complex frequencies of the free plasma oscillations. Therefore, the resonant frequencies, f n , and the loaded quality factors, Q n , of the plasma oscillations may be computed using the formulas fn=Re(ωn)/false(2π), Qn=Re(ωn)/true(2Im(ωn)true). …”
Section: Initial Formulasmentioning
confidence: 99%
“…It is clear that the roots, ω n , of the equation 1/Annormale(ω)=0 for each multipole excitation of the nanoparticle are the complex frequencies of the free plasma oscillations. Therefore, the resonant frequencies, f n , and the loaded quality factors, Q n , of the plasma oscillations may be computed using the formulas fn=Re(ωn)/false(2π), Qn=Re(ωn)/true(2Im(ωn)true). …”
Section: Initial Formulasmentioning
confidence: 99%
“…Yoshiaki Fuda et al studied the Q factor of multilayer piezoelectric vibrators made from a PbZrTiO 3 ceramic material with internal electrodes, and found that an increase in the number of internal electrodes led to a decrease in the Q factor [21], but the reason given for this result was insufficient. Belyaev et al took a resonator comprising of a halfwavelength dielectric layer that was covered from both sides by quarterwavelength layers as the research objective and explored the Q factor dependencies on both the number of the dielectric layers and their optical properties [22]. The proposed approach enables one to determine the necessary number of dielectric layers covering the resonator needed to achieve the required Q factor.…”
Section: Introductionmentioning
confidence: 99%